A robust propulsion layout for underwater vehicles with enhanced manoeuvrability and reliability features. (August 2018) - Pugi, Luca; Pagliai, Marco; Allotta, Benedetto
Design of autonomous underwater vehicles is deeply influenced by required mission specifications. In particular, some activities like inspection of offshore plants or harsh marine environments require underwater vehicle with high autonomy, good propulsion performances and manoeuvrability. These features are deeply influenced by design and performances of the propulsion system. In particular, performances of underwater vehicles (both remotely operated and autonomous) are deeply influenced by four quadrants performances of propellers and by complex fluid dynamics interactions that are difficult to be, even roughly, evaluated. In this work, a study of a reconfigurable propulsion layout and its comparison with a conventional one is introduced. In particular, this study is also focused on modelling techniques that should really represent a reasonable trade-off in terms of accuracy and involved computational resources for fast prototyping and simulation of this kind of mechatronic systems.